™Germination Index (GI) and Germination Speed Index (IVG) of cherry tomato (Solanum lycopersicum var. cerasiform, solanaceae) seeds grown in pots under different substrates / ™Índice de germinação (IG) e índice de velocidade de germinação (IVG) do tomate cereja (Solanum lycopersicum var. cerasiforme, solanaceae) cultivadas em vasos sob diferentes tipos de substratos - Luiz Francisco Tavares da Silva; Thaynnara Paula dos Santos Lira; Victória Polyana Azevedo Araújo; Lívia Gibrinde Barbosa; Letícia Paula Barros Lima; Rubens Pessoa de Barros (Universidade Estadual de Alagoas, 2020)
The objective of this study was to evaluete the germination (IG) and germination rate (IVG) indexes of Cherry Tomato (Solanum lycopersicum var. cerasiforme) on different substrates in protected environment. The research area was in the greenhouse of the State University of Alagoas, Campus I, in Arapiraca-AL during the months of March to April / 2019. The substrates used were fine sand, washed sand, agricultural soil and Bioplant®. The sowing occurred in plastic vessels, and were performed with 5 replicates in each soil type, totaling 20 samples. The GI and IGV of each sample were analyzed in the period of 30 days. It was possible to identify that the cherry tomato showed better IG and IGV in the substrates Areia Fina and Bioplant.